Age Specificity in Explicit and Implicit Endorsement of Prescriptive Age Stereotypes - de Paula Couto, M. Clara; Huang, Tingting; Rothermund, Klaus (Frontiers in Psychology, 2022)
In this study, we investigated explicit and implicit endorsement of prescriptive age stereotypes. To achieve that, we captured endorsement of a wide range of prescriptive expectations targeting both younger (younger adults are expected to be ambitious, eager to learn, unconventional, respectful) and older (older adults are expected to stay active, to be generous, dignified, and wise) people. Younger (n = 58, 50% female, Mage = 26.07 years, SD = 3.01) and older adults (n = 75, 44% female, Mage = 66.69 years, SD = 4.63) participated in the study. We assessed implicit endorsement of prescriptive age stereotypes with the Propositional Evaluation Paradigm (PEP) and used a direct measure to assess explicit endorsement. In general, we found strong support for age-specificity in both explicit and implicit endorsement of prescriptive age stereotypes: Sentences ascribing expectations for young/old to the respective age group (e.g., “young should be ambitious”; “old should be wise”) were endorsed much more strongly than sentences in which expectations for young/old were ascribed to the other age group (e.g., “old should be ambitious”; “young should be wise”). Age group differences in the endorsement of prescriptive age stereotypes were found. Compared to younger participants, older participants showed stronger endorsement for prescriptive beliefs targeting both younger and older targets. Explicit and implicit endorsement of prescriptive age stereotypes did not correlate with one another, thus revealing they might assess independent belief systems with different predictive potential.